Preclinical Evaluation of Carfilzomib for Infant KMT2A-Rearranged Acute Lymphoblastic Leukemia - Cheung, Laurence C.; de Kraa, Rebecca; Oommen, Joyce; Chua, Grace-Alyssa; Singh, Sajla; Hughes, Anastasia M.; Ferrari, Emanuela; Ford, Jette; Chiu, Sung K.; Stam, Ronald W.; Kees, Ursula R.; Malinge, Sébastien; et al. (Frontiers in Oncology, 2021)
Background: Infants with KMT2A-rearranged B-cell precursor acute lymphoblastic leukemia (ALL) have poor outcomes. There is an urgent need to identify novel agents to improve survival. Proteasome inhibition has emerged as a promising therapeutic strategy for several hematological malignancies. The aim of this study was to determine the preclinical efficacy of the selective proteasome inhibitor, carfilzomib, for infants with KMT2A-rearranged ALL. Methods: Eight infant ALL cell lines were extensively characterized for immunophenotypic and cytogenetic features. In vitro cytotoxicity to carfilzomib was assessed using a modified Alamar Blue assay with cells in logarithmic growth. The Bliss Independence model was applied to determine synergy between carfilzomib and the nine conventional chemotherapeutic agents used to treat infants with ALL. Established xenograft models were used to identify the maximal tolerated dose of carfilzomib and determine in vivo efficacy. Results: Carfilzomib demonstrated low IC50 concentrations within the nanomolar range (6.0-15.8nm) across the panel of cell lines. Combination drug testing indicated in vitro synergy between carfilzomib and several conventional chemotherapeutic agents including vincristine, daunorubicin, dexamethasone, L-asparaginase and 4-hydroperoxycyclophosphamide. In vivo assessment did not lead to a survival advantage for either carfilzomib monotherapy, when used to treat both low or high disease burden, or for carfilzomib in combination with multi-agent induction chemotherapy comprising of vincristine, dexamethasone and L-asparaginase. Conclusions: Our study highlights that in vitro efficacy does not necessarily translate to benefit in vivo and emphasizes the importance of in vivo validation prior to suggesting an agent for clinical use. Whilst proteasome inhibitors have an important role to play in several hematological malignancies, our findings guard against prioritization of carfilzomib for treatment of KMT2A-rearranged infant ALL in the clinical setting.